Tubercular Spondylitis: A Rare Complication of BCGosis Masquerading as Metastasis on 18F-PSMA-1007 PET/CT. (12th March 2022) - Bohil, Amit; Seshadri, Nagabhushan; Rathi, Nitika; Fernando, Rashika; Vinjamuri, Sobhan
Abstract: BCGosis is a rare complication of intravesical BCG immunotherapy as adjuvant therapy for urinary bladder cancer manifesting in the form of disseminated tuberculosis or organ-specific tuberculosis, rarely involving the vertebra. PSMA is overexpressed in prostate cancer but also expressed in a variety of benign and malignant conditions. We present a patient with incidental detection of abnormal uptake in a vertebral lesion during assessment of prostate cancer with 18 F-PSMA PET/CT, subsequently proven to be vertebral osteitis, likely due to BCG immunotherapy. The case highlights the role of interdisciplinary patient assessment to confirm nature of abnormal foci on 18 F-PSMA PET/CT.